Mycotoxins in foodstuffs - Weidenbörner, Martin (Springer US Imprint: Springer, 2013)
Mycotoxin contamination of food occurs as a result of crop invasion by field fungi such as Fusarium spp. and Alternaria spp., or storage fungi such as Aspergillus spp. and Penicillium spp., which can grow on/in stored commodities and are able to produce mycotoxins. In the worst case, these fungi produce secondary metabolites called mycotoxins, which can be very harmful to humans and animals when for example they are consumed through food due to their various negative effects on several organs in both humans and animals. The present book gives a basic overview of the main mycotoxins in food. It lists the predisposition of a foodstuff for mycotoxin contamination, the degree of contamination, concentration, and country of detection / origin for each case of mycotoxin contamination of food. Major updates to this second edition include: - More than 750 new publications concerning mycotoxins in foodstuffs (1665 literatures at all) - A single chapter overview of mycotoxin(s) in the corresponding foodstuff - The co-occurrence of mycotoxins in a foodstuff has been listed where possible - Numerical and alphabetical literature - Organic and conventional foods of a publication have been listed separately where possible - Numerous entries described in much greater detail - Each analyzed foodstuff has a separate entry per year where possible